Thermal behavior of ara double dagger a oil (Psidium cattleianum Sabine) - Kobelnik, Marcelo; Cassimiro, Douglas Lopes [UNESP]; Dias, Diogenes dos Santos [UNESP]; Ribeiro, Clovis Augusto [UNESP]; Crespi, Marisa Spirandeli [UNESP] (Springer, 2012)
The ara double dagger A is a well-known fruit, which belongs to the Myrtaceae family, Psidium cattleianum Sabine species, frequently found in the southern region of Brazil. The extraction of ara double dagger a oil was carried out from seeds, and the fatty acid profile of this oil indicates the predominant presence of linoleic acid (81.38%). Thermogravimetry, derivative thermogravimetry, and differential scanning calorimetry (DSC) were used to characterize this oil. In addition, this oil was evaluated by DSC from 25 to -60 A degrees C, where the crystallization behavior was verified. Details concerning thermal decomposition as well as data of kinetic parameters of these stages have been described here. The kinetic behavior of the thermal decomposition was evaluated from several heating rates with mass samples of 5 and 20 mg in open crucibles under nitrogen and synthetic air atmospheres.
Keywords: Araca oil; Thermal behavior; Kinetic parameters; Crystallization